Long-term Follow-up of Patients with Tubulointerstitial Nephritis and Uveitis (TINU) Syndrome. (19th May 2018) - Sobolewska, Bianka; Bayyoud, Tarek; Deuter, Christoph; Doycheva, Deshka; Zierhut, Manfred
ABSTRACT: Purpose : To evaluate the response to treatment in patients with tubulointerstitial nephritis and uveitis (TINU) syndrome over a long-term follow-up period. Methods : Nine patients with TINU syndrome were retrospectively reviewed. The mean follow-up was 54.8 months (range: 24–133 months). Results : The mean number of recurrences per year declined from 1.7 in the 1st year to 0.66 in the 2nd year of treatment. The ocular inflammation responded to local corticosteroids in two patients, systemic corticosteroids in two patients, immunosuppressive therapy in four patients, and anti-TNF-α blocking agent in one patient. The therapy could be discontinued in six (67%) patients after a mean treatment period of 29.5 months. In five patients, remission with the recurrence-free period of 12.8 months was achieved. Conclusions : TINU syndrome was characterized by limited responsiveness to corticosteroid therapy and less by severe complications. A long-term course of immunosuppressants or biologics was necessary to control the uveitis and led to induction of remission.